Everyday life & consumer culture in 18th-century Damascus - Grehan, James (Publications on the Near East, University of Washington., 2007)
"In assessing the magnitude of social change in modern times, we have few benchmarks from the period preceding the onset of modernity in the nineteenth century. This informative study will make possible more precise cultural and economic comparisons between different parts of the world as it stood on the brink of a radically new economic and political order. The book's focus on a little-examined period and region will appeal to scholars and students of urban social history and Arab popular culture."--Jacket